SPORT AND ITS IMPACT ON THE HUMAN BODY - Sotivoldiev Qodirjon, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
The article presents the results of a study aimed at revealing the influence of sport on the human body and on everyday life.